МОДЕЛІ ТА МЕТОДИ ДОСЛІДЖЕННЯ СИСТЕМ МАСОВОГО ОБСЛУГОВУВАННЯ МАРКІВСЬКОГО ТИПУ В УМОВАХ СТОХАСТИЧНОЇ ПЕРІОДИЧНОСТІ ТА ЇХНЄ ЗАСТОСУВАННЯ В ЕНЕРГЕТИЦІ - Приймак, М.В.; Мацюк , О.В.; Маєвський , О.В.; Прошин , С.Ю. (Інститут електродинаміки НАН України, Київ, 2014)
The main stages of queuing systems development are highlighted and represented the criteria of division of these sys[1]tems onto Markov and non-Markov types. On the base of these positions we have established that power systems and power consumption systems can be treated as queuing systems of Markov type. The model of graphs of electrical power consumption as periodical Markov chain is grounded. The method of evaluation of transitional matrices is examined, and on concrete example of power consumption, such evaluations are retrieved. References 8, table 1, figures 3.